2009
DOI: 10.1111/j.1540-8159.2009.02432.x
|View full text |Cite
|
Sign up to set email alerts
|

A Viewpoint on the Impact of Device Advisories on Patient‐Centered Outcomes

Abstract: Device advisories due to potential hardware failure comprise one of the downsides of implantable cardioverter defibrillator (ICD) therapy. The impact of advisories on patient-centered outcomes has largely been overlooked. We examined the impact of ICD advisories on patient-centered outcomes via a systematic literature review. PubMed was searched in the period from 1980 to present using a combination of at set of a priori search terms. The reference lists of the included papers were searched by hand. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…However, all of these papers examined small numbers of patients (33–86 patients, see Ref. 17 for review).…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these papers examined small numbers of patients (33–86 patients, see Ref. 17 for review).…”
Section: Discussionmentioning
confidence: 99%
“…The 2 prospective studies in this meta‐analysis showed that device advisory may lead to increased anxiety and decreased confidence in the device. In case control studies, patients with devices under a class I advisory reported poorer quality of life than those with a device under a class II advisory 26 …”
Section: Discussionmentioning
confidence: 99%
“…Hedblad et al (30), who studied causes for failure to reach target goals in the management of hypertension, found that frequent blood pressure measuring and patient communication with physicians, a PCC approach, correlated with attaining blood pressure goals. Pedersen et al (31) have discussed the need to consider a PCC approach to patients with implanted devices (32). They suggested that PCC involving behavior measures be included in device databases.…”
Section: Purpose and Backgroundmentioning
confidence: 99%